STUDENTS’ RESPONSES TOWARD THE USE OF SCIENTIFIC APPROACH THROUGH BLOGSPOT MEDIA IN TEACHING WRITING - Rizal Nurrudin; Yanuarti Apsari (PROJECT (Professional Journal of English Education), 2023)
This research discovers students’ responses toward the use of scientific approach through Blogspot media in teaching writing skill. This research is qualitative research. The participants of this research were 30 students of Senior high school in Cianjur. In obtaining the data, questionnaire was employed as the research instruments. The findings of this research indicated that the students’ responses have positive perception on the use of scientific approach through blogspot media. Students felt that learning writing descriptive text using Blogspot make students understand the material easily, Learning writing descriptive text using scientific approach trough Blogspot is more interesting. Thus, learning writing by using scientific approach through blogsopt can motivate the students and  make them participate actively in the classroom.